Combined deletion of the fibronectin-type III domains and the stalk region results in ligand-independent, constitutive activation of the Interleukin 6 signal-transducing receptor gp130. (October 2018) - Lamertz, Larissa; Floss, Doreen M.; Scheller, Jürgen
Abstract: Gp130 is the common receptor within the Interleukin 6 cytokine family. Gp130 consists of 6 extracellular domains followed by a small stalk region connecting the last extracellular domain with the trans-membrane domain. Whereas the first three extracellular domains bind to IL-6-type cytokines, the domains 4–6 are needed for correct positioning of the intracellular domains to facilitate Janus kinase activation after cytokine binding. Interestingly, deletion within the cytokine-binding domain resulted in cytokine-independent constitutive activation of mutant gp130 receptors. Here, we tested the hypothesis, if deletions of the stalk region and/or domains 4–6 of gp130 might also result in constitutive receptor activation. Shortening of the stalk region of gp130 alone did, however, not result in constitutive receptor activation, whereas a gp130 receptor deletion variant only consisting of the three N-terminal cytokine binding domains but lacking all FNIII domains was biologically inactive. Importantly, combined deletion of the three FNIII domains plus shortening of the stalk region of gp130 resulted in ligand-independent, constitutive receptor activation of gp130.